LINGUISTIC LANDSCAPE IN TRADITIONAL CULINARY TOURISM AT KAMPOENG LAMA DELISERDANG - Rahmat Darmawan; Dewi Nurmala; Gumarpi Rahis Pasaribu (Rahis Cendekia Indonesia, 2024)
This study investigates the linguistic landscape within the traditional culinary tourism destination of Kampoeng Lama, located in Pantai Labu, Deli Serdang, North Sumatra. Utilizing a qualitative approach, data were collected through participant observation and documentation methods based on Sudaryanto’s simak libat cakap technique. The research explores verbal interactions and analyzes visual elements of public signage, including shop signs, banners, menus, and promotional slogans. The findings reveal a diverse use of languages, ranging from monolingual, bilingual, to multilingual displays, with a focus on the symbolic and communicative functions of language. The analysis highlights how language is utilized to reflect local cultural identity while promoting the area's appeal as a culinary destination. Signs written in Bahasa Indonesia emphasize inclusivity and emotional connection, with strategic visual designs incorporating traditional elements such as bamboo and natural tones to convey authenticity. Local terms and creative wordplay further enrich the cultural experience for visitors, fostering a sense of nostalgia and pride. The study underscores the role of language in shaping the visitor experience, showcasing Kampoeng Lama as a site where cultural preservation and modern marketing strategies intersect. This linguistic landscape not only serves communicative purposes but also symbolizes the area's cultural and economic vitality. By bridging tradition and innovation, Kampoeng Lama offers an immersive experience that appeals to a wide range of audiences, establishing itself as a hub for cultural and culinary tourism